Towards hydrogen and halogen bonded frameworks based on 3, 5-bis(triazolyl)pyridinium motifs. Issue 17 (7th April 2022) - Foyle, Émer M.; Tay, Hui Min; White, Nicholas G.
Abstract : Construction of supramolecular assemblies using hydrogen and halogen bonding between anions and the 3, 5-bis(triazolyl)pyridinium motif was investigated. Abstract : We attempted to use hydrogen, iodo and seleno 3, 5-bis(triazolyl)pyridinium (btp ) motifs to form 3D supramolecular frameworks assembled by hydrogen, halogen or chalcogen bonding to anions. Initially, we prepared flexible ditopic and tetratopic receptors where the pyridinium nitrogen atom was functionalised with a benzylic group but were unable to crystallise extended frameworks. We subsequently developed the use of Zincke methodology to prepare rigid ditopic and tetratopic hydrogen and halogen bonding tectons, and were able to crystallise the sulfate derivative of a tetratopic receptor, although unfortunately this did not have the desired open framework. Several crystal structures were obtained with the receptors and monovalent anions, including one containing an unusually short iodotriazole⋯Cl − halogen bond. Generally, the btp triazole groups show a tendency to rotate away from the desired conformation and it appears that this may contribute to difficulties in obtaining 3D frameworks even when the receptors have a rigid core.